Need Analysis for Digital Transformation of Nutrition Care Process - Miftahul Jannah; Arisanty Nur Setya Restuti; Muhammad Iqbal (Puslitbang Sinergis Asa Professional, 2023)
The Nutrition Care Process (NCP) is a systematic problem-solving method that nutrition professionals use to think critically and make decisions that address practice-related problems. Nutrition Care Process consists of 4 systematic steps, namely nutrition assessment, nutrition diagnosis, nutrition monitoring, and evaluation. Implementation of NCP in fact faces some barriers, such as much time needed and incomplete documentation. Digitalization of NCP is expected to be a solution to overcome the barriers. This study aimed at investigating the requirement of hospitals and clinics toward NCP digital. This was a qualitative study where the design was an exploration case study. The number of informants was 5 interviewees who work as dietitians and nutritionist in some hospitals and clinic. The data were collected by focus group discussion. The data were analyzed using thematic analysis. Five primary themes emerged as the main design needed in NCP digital. The themes are automatic calculation and categorization of nutrition assessment data, automatically selecting of nutrition diagnosis, integration with the diet leaflet for patients, and integration with medical record and other health care workers’ systems. In conclusion, the dietitians considered that NCP digital had some advantages to accelerate and improve their work. The dietitians had the intention to accept NCP digital and expected it to be a solution to making their work easily and faster.